Estimating compound growth rate, instability index and annual fluctuation of cotton in Pakistan - Rani, Saima; Habib, Nusrat; Raza , Irum; Zahra , Naheed (Asian Journal of Agriculture and Rural Development, 2017)
The key concern of this research is to assess the growth, instability and annual fluctuations of cotton during last three decades in Pakistan. The time series data on area, production and yield of cotton is collected for the year 1981 to 2015 from different issues of agricultural statistics of Pakistan. The results depict that positive growth rates on area, production and yield of cotton expanding over time due to involvement of private companies. The growth rate of yield is 2.65 followed by 0.88 growth of yield in cotton area in Pakistan. While analyzing the data the instability is high in production and low in area of cotton in Pakistan that mainly due to insect and pest attack on crop. Production annual fluctuation of cotton is high and not a consistent during study period especially in 1981-90. The fluctuation highly increased in 1984-85 and lowest during the year 1983-84. In the cotton area fluctuation highest in 1995-96 and lowest in 2010-11 in country. The yield of cotton is highly fluctuating during the year 1984-85 and lowest in 1983-84. There should be some control over the diseases this will reduce the fluctuation for production in cotton. Easy availability of modern factor inputs and sustained supply will reduce area instability largely.